Border Apprehensions and Federal Sentencing of Hispanic Citizens in the United States - Simone Bertoli; Morgane Laouénan; Jérôme Valette (Institute of Labor Economics (IZA), 2023)
We provide evidence that Hispanic citizens receive significantly longer sentences than non-Hispanic citizens in the Federal Criminal Justice System in the United States when a higher number of illegal aliens are apprehended along the southwest border. Apprehensions can increase the salience of Hispanic ethnic identity, which is associated with persistent negative stereotypes, and can also deteriorate attitudes toward Hispanics. We rule out concerns that apprehensions might be conveying legally relevant information to judges. Thus, we provide direct evidence for time-varying discrimination toward Hispanic defendants. Our estimated effect is only at play for defendants without a heavy previous criminal record.
Keywords: K42; J15; F22; 330; immigration; ethnic identity; discrimination; attitudes; salience; sentences